Synthesis and characterization of micropous carbon adsorbents from oil palm shell - Imanurezeki, Mohamad (2009)
Carbon adsorbents are microporous in structure that can be produced from any raw materials that contain high carbon contents such as wood and coal. The increasing research in carbon adsorbents because of its high adsorption capacities. This research is conducted to study the performance of carbon adsorbents produced from oil palm shell. The preparation of carbon adsorbents consists of carbonization and activation process. This study revealed that the parameters of carbonization and activation process such as temperature affect the carbon adsorbents properties such as pore size, pore volume and surface area. Previous research has proved that the initial properties of carbon adsorbents produced will affect the effectiveness of adsorption and desorption analysis. The results also revealed that the optimum carbonization and activation temperature of 500°C in the preparation of carbon adsorbents significantly enlargement of pores size and efficient for adsorption-desorption applications. This study showed that oil palm shell carbon adsorbents produced from activation temperature of 700°C possesses the largest surface area and micropore volume among the adsorbents tested. Adsorption and desorption of gaseous was observed by the percentage adsorption and desorption of nitrogen and LPG in experimental rig and two types of test bed model. Study shown that gas adsorption and desorption analysis is appropriate to determine the surface area and pore size distribution of carbon adsorbents. In addition, the oil palm shell carbon adsorbents are compared with carbon adsorbents produced from coconut shell and commercial activated carbon and the used of LDPE plastic bags as additive to existing carbon adsorbents in terms of nitrogen and LPG adsorption-desorption analysis. It was examined that the LDPE plastic bag might block or shrink the pore structure of the-char. Other parameters and adsorptiondesorption capability of each carbon adsorbents samples have been defined and discussed. Lastly, the impact of carbon adsorbents in the application of LPG and methane storage tank was studied. The application of oil palm shell carbon adsorbents increased the amount of LPG and methane in storage tank.